Mitigating machinery's environmental impact in palm oil plantations for enhanced business performance - Amira Nur Alia, Azmi; Nur Sofia Nabila, Alimin; Bathaei, Ahmad (Penerbit Universiti Malaysia Pahang, 2025)
This study highlights the importance for YP Plantation Holdings Sdn Bhd (YPPH) to maintain the use of machinery in palm oil plantations without damaging the environment. One of the keys to achieving such goal is to conduct regular inspections and maintenance to ensure that all machinery is working properly and efficiently, thus avoiding costs associated with breakdown and repair. It is also important for the machinery to comply with environmental regulations. This will not only promote environmentally friendly operations but also establish a positive impression among environmentally conscious stakeholders. In conclusion, proper maintenance of equipment and machines will help YPPH to save costs and become an environmentally friendly entity, thus ensuring its long-term success in the palm oil industry.